Cardiovascular impairment in Shiga-toxin-2-induced experimental hemolytic–uremic syndrome: a pilot study - Neu, Charles; Wissuwa, Bianka; Thiemermann, Christoph; Coldewey, Sina M. (Frontiers in Immunology, 2023)
Hemolytic-uremic syndrome (HUS) can occur as a systemic complication of infection with Shiga toxin (Stx)-producing Escherichia coli (STEC). Most well-known aspects of the pathophysiology are secondary to microthrombotic kidney disease including hemolytic anemia and thrombocytopenia. However, extrarenal manifestations, such as cardiac impairment, have also been reported. We have investigated whether these cardiac abnormalities can be reproduced in a murine animal model, in which administration of Stx, the main virulence factor of STEC, is used to induce HUS. Mice received either one high or multiple low doses of Stx to simulate the (clinically well-known) different disease courses. Cardiac function was evaluated by echocardiography and analyses of biomarkers in the plasma (troponin I and brain natriuretic peptide). All Stx-challenged mice showed reduced2 This is a provisional file, not the final typeset article cardiac output and depletion of intravascular volume indicated by a reduced end-diastolic volume and a higher hematocrit. Some mice exhibited myocardial injury (measured as increases in cTNI levels). A subset of mice challenged with either dosage regimens showed hyperkalemia with typical electrocardiographic abnormalities. Myocardial injury, intravascular volume depletion, reduced cardiac output as well as arrhythmias as a consequence of hyperkalaemia may be prognosis-relevant disease manifestations of HUS, the significance of which should be further investigated in future preclinical and clinical studies.